Hematologi dan Kimia Klinik Darah Kambing Peranakan Etawah yang Diberi Pakan Produk Sampingan Pertanian dan Enzim Optizym (HEMATOLOGY AND BLOOD CLINICAL CHEMISTRY OF ETAWAH GOAT CROSSBRED-FED AGRICULTURE BY PRODUCTS SUPPLEMENTED WITH OPTIZYM ENZYME) - Yupardhi, Wayan Sayang; Oka, I Gusti Lanang; Mantra, Ida Bagus (Jurnal Veteriner; Vol 14 No 1 (2013), 2013)
In Indonesia including Bali island until now, a lot of Etawah Goat Crossbred raised by farmers. Inthe island, there was  lots of  agriculture by products available which were not much used yet for animalfeed. There is an opportunity the product were supplemented with Optizym enzyme to  feed the animal.The enzyme was a cellulotic one. The objective of this experiment was to study hematology (packaged cellvolume, hemoglobin, erythrocytes, leukocytes, neutrophil, lymphocyte, monocyte, eosinophil, sedimentationrate) and clinical chemistry of blood (creatinine, urea, serum glutamic piruvat transaminase, serum glutamicoxaloacetic transaminase, glucose, and cholesterol). The experiment was conducted for 2 months at Bukit-Jimbaran, Badung, Bali. Measurements were conducted  on the packaged cell volume with the method ofmicrohematocrite, hemoglobin with the method of Hematin (Hemoglobinometer or Hemometer Sahli),erythrocytes and leukocytes with the method of Hemocytometer (improved Neubaeur), differential ofleukocytes (neutrophil, lymphocyte, monocyte, eosinophil) with the method of slide; and blood sedimentationrate with the method of Westergreen, while measurements of the creatinine, urea, serum glutamic piruvattransaminase, serum glutamic oxaloacetic transaminase, glucose, and cholesterol were conducted with Reflotron Plus modified Reflovet Plus (Roch).Data were analyzed with Analysis of Variance. Results ofthe experiment showed that supplementation of the optizym for 0,25 kg and 0,50 kg in every 100 kg basaldiet of agriculture by products (unconventional) were not increased significantly on the packaged cellvolume, hemoglobin, total erythrocytes, total leucocytes, neuthrophil, lymposite, monocyte and the samething was also occurred on serum glutamic piruvat transaminase, serum glutamic oxaloacetictransaminase, glucose, and cholesterol of the animals (P > 0.05) compared to the untreated one; while therest (blood sedimentation rate, creatinine, and urea) were on the other way around (P < 0.05). However,they were not affected their performances. The animals still look healthy.  It can be concluded that thesupplementation of the optizym in this case was no effect to hematology and clinical chemistry of blood.
Keywords: Etawah Goat Crosbred, optizym enzyme, hematology, clinical chemistry of blood